Probiotic characteristics and whole genome sequence analysis of Lactiplantibacillus plantarum ZFM518 isolated from infant feces - Yingjuan Zhang; Qingqing Zhou; Ziqi Chen; Zhongdu Ye; Ying Jin; Ping Li; Qing Gu (Food Frontiers)
Abstract Emerging research has shown that lactic acid bacteria in the intestines of newborns play a beneficial role in the growth, immune function, and metabolism of infants after birth. In this study, four strains of Lactobacillus were isolated from fecal samples of newborns, and a safe Lactiplantibacillus plantarum ZFM518 (ZFM518) strain was obtained after the screening, which showed excellent antibacterial activity and adhesion potential. The strain exhibited excellent ability to survive in acidic environments, simulated gastric juice, and simulated intestinal environments, respectively. ZFM518 had a bacteriostatic zone of 31.12 ± 0.33 mm against Staphylococcus aureus, a hydrophobic rate of 76.97% ± 3.35%, and a survival activity of 96.54% ± 0.14% under a simulated intestinal fluid environment. Moreover, ZFM518 can produce up to 161.11 ± 9.67 ng/mL of folate. A genome‐wide investigation of ZFM518 revealed that the majority of its genes were involved in the metabolism of amino acids, carbohydrates, adhesion, immunological defense, and antibacterial activity. In addition, only one antibiotic resistance gene of the antimicrobial peptide was annotated. These results indicate that ZFM518 is a new strain with a strong comprehensive ability and probiotic potential. This study can provide practical support for screening potential probiotics from infant feces and provide a theoretical basis for developing probiotic resources.